(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the relationship between adhesive capsulitis and serum vitamin D levels. Materials and Methods: Patients who were diagnosed with primary adhesive capsulitis between 2015 and 2019 and had regular follow-up data were retrospectively evaluated. Age, gender, body mass index, affected side, disease duration, serum 25-OH vitamin D levels, range of shoulder motion, the Visual Analog Scale (VAS) score, the Constant-Murley score, and the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire score were evaluated. Patients with a diagnosis of diabetes, history of rheumatic diseases, presence of cervical pathologies, history of fracture and/or shoulder surgery, history of infection, and full-thickness rotator cuff tear were excluded from the study. The serum 25 (OH) D levels below 20 ng/ml were accepted as deficiency. The patients were divided into two groups according to the serum vitamin D level (Group 1 if 20 ng/mL and Group 2 if ≥20 ng/mL). The VAS score, functional scores, range of motion (flexion, abduction, external and internal rotation) of the patients in the two groups were compared.Results: Of the 74 patients included in the study, 59 (79.2%) were female and 15 (20.3%) were male, with a mean age of 50.6 ± 9.74 years. The mean duration of pain was 8.21 ± 2.3 months. The serum vitamin D level was below 20 ng/ml in 43 patients (58.1%) who were then allocated to Group 1, and Group 2 comprised 31 patients. The mean VAS score was 7.8 for Group 1 and 5.2 for Group 2. The mean Constant-Murley and DASH scores were 54.4 ± 15.9 and 21.6 ± 9.78, respectively in Group 1 and 52.04 ± 12.2 and 24.3 ± 6.4, respectively in Group 2. No significant difference was observed between the groups according to the range of joint motion, Constant scores, or DASH scores. Conclusion: Vitamin D deficiency may be associated with shoulder pain in patients with adhesive capsulitis. However, the serum vitamin D level had no effect on the functional results. Conclusion: In the present study, serum CRP, TNF-α and H.pylori IgA levels were significantly higher than normal pregnant women.